2015
DOI: 10.1002/chem.201502798
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Properties, and Two‐Dimensional Adsorption Characteristics of 5‐Amino[6]hexahelicene

Abstract: A convergent synthesis of racemic 5-amino[6]hexahelicene is described. Cross-coupling reactions are used to assemble a pentacyclic framework, and a metal-catalyzed ring-closure comprises the final step. The enantiomers were separated by means of chromatography and the absolute configurations were assigned by comparison of the CD spectra with hexahelicene. The t1/2  value for racemization at 210 °C was approximately 1 hour. Scanning tunneling microscopy (STM) measurements were carried out on enantiopure and rac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 48 publications
(82 reference statements)
0
22
0
Order By: Relevance
“…301 The self-assembly of enantiopure (M) and (rac)-297 on Au(111) under UHV conditions was further investigated in 2016 (Figure 40a2). 295 The authors observed two rotational domains formed by rows of dimers oriented along the <1-11> Au crystallographic directions for the enantiopure aminohelicene being formed, according to DFT calculations, by flat-lying molecules in which the NH 2 groups govern the interaction with the surface (i.e., "N down"), whereas the C6 rings pack closely to maximize van der Waals interactions between neighboring molecules. Regarding the racemic compound, it showed the emergence of two enantiomorphous domains which are rotated by 6° with respect to the <1-11> crystallographic directions and have a double-row structure.…”
Section: Applications Of Carbocationic Azahelicenesmentioning
confidence: 99%
“…301 The self-assembly of enantiopure (M) and (rac)-297 on Au(111) under UHV conditions was further investigated in 2016 (Figure 40a2). 295 The authors observed two rotational domains formed by rows of dimers oriented along the <1-11> Au crystallographic directions for the enantiopure aminohelicene being formed, according to DFT calculations, by flat-lying molecules in which the NH 2 groups govern the interaction with the surface (i.e., "N down"), whereas the C6 rings pack closely to maximize van der Waals interactions between neighboring molecules. Regarding the racemic compound, it showed the emergence of two enantiomorphous domains which are rotated by 6° with respect to the <1-11> crystallographic directions and have a double-row structure.…”
Section: Applications Of Carbocationic Azahelicenesmentioning
confidence: 99%
“…The synthesis of heptahelicene 2‐carboxylic acid has been described recently by means of cross‐coupling followed by [2+2+2] cyclization . A straightforward convergent synthesis of 5‐aminohexahelicene has recently been described by some of our group . We wished also to develop a strategy for placement of a carboxyl group in a central position on the helicene periphery using synthetic knowledge already gained from the cross‐coupling approach we had developed .…”
Section: Resultsmentioning
confidence: 99%
“…A straightforward convergent synthesis of 5‐aminohexahelicene has recently been described by some of our group . We wished also to develop a strategy for placement of a carboxyl group in a central position on the helicene periphery using synthetic knowledge already gained from the cross‐coupling approach we had developed . However, despite much effort (see the Supporting Information) a synthesis of [6]hexahelicene‐7‐carboxylic acid 1 (Figure ) based on the route of ref.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations